Effectiveness of the Basic Infection Control Skills License (BICSL) Training Program on Nurses' Knowledge, Attitudes, and Practices in Makkah, Saudi Arabia - Azizah Banafi; Noor Mastura Mohd Mujar (The Open Nursing Journal, 2026)
Introduction Healthcare-associated infections (HCAIs) remain a major global health concern. In Saudi Arabia, the Basic Infection Control Skills License (BICSL) program was introduced to standardize infection prevention and control (IPC) training among healthcare workers. However, evidence on its effectiveness among nurses remains limited. Methods A multicenter, quasi-experimental, one-group pre-post study was conducted among 360 nurses from 5 public hospitals in Makkah, Saudi Arabia, during the 2024 BICSL implementation cycle. All participants received the same 3-day, in-person BICSL intervention; no random allocation or concurrent comparison group was used. A validated self-administered questionnaire assessed knowledge, attitude, and self-reported practice before and immediately after training. Paired t-tests, Wilcoxon signed-rank tests, effect sizes, reliability analyses, baseline-adjusted models, change-score models, and sensitivity analyses were conducted. Results Knowledge scores increased from 8.54 ± 2.03 to 10.71 ± 1.79, attitude scores from 2.30 ± 0.77 to 2.70 ± 0.51, and practice scores from 4.48 ± 1.91 to 5.90 ± 1.85 (all p < 0.001). Wilcoxon tests confirmed the pre-post differences. Cohen's dz values were 0.72 for knowledge, 0.43 for attitude, and 0.55 for practice. In adjusted analyses, improvement in knowledge remained significantly associated with post-training practice and practice improvement. Discussion The findings suggest that structured BICSL training may strengthen nurses' IPC-related knowledge and self-reported practice. However, interpretation should remain cautious because the one-group pre-post design cannot exclude testing effects, seasonal influences, concurrent IPC activities, or social desirability bias. Conclusion BICSL training was associated with improved knowledge, attitudes, and practices (KAP) scores among nurses in hospitals in Makkah. Future evaluations should include control groups, longer follow-up, observational audits, and IPC outcome indicators.